Intratest Reliability of the Modified 505 Test in Adult Male Professional Soccer Players - Aedo-Munoz, E (Editura Universitatii din Pitesti, 2024)
Objective: This study assessed the intratest reliability of the modified 505 180° change of direction test in adult male professional players. Methods: 37 adult male players (age= 23.4±4.88 years, body mass= 75.7±6.46 kg, height=176.2±6.74 cm), affiliated with a professional club in the Chilean first B division, performed 4 attempts (two per profile) of the modified 505 test. Absolute reliability was evaluated using coefficient of variation, while relative reliability was assessed via the intraclass correlation coefficient, with a 95% confidence interval (CI). Bland-Altman graphs and statistics. Results: Acceptable absolute reliability was found in the right and left profile (CV=1.82 and 2.16% respectively). Poor to good relative reliability was found in the right profile (ICC=0.586, 95% CI=0.335 to 0.759) and poor to moderate reliability in the left profile (ICC=0.562, 95% CI=0.309 to 0.742). Bland-Altman statistics found a Bias and standard deviation of Bias in the right profile of 0.015±0.79 seconds and in the left profile of 0.03±0.091 seconds. Conclusion: From the results it is concluded that the modified 505 test has moderate relative reliability and acceptable absolute reliability. In practical terms, this means that trainers should evaluate more than 1 attempt per profile. The reliability of the test should be taken into consideration to analyze subsequent changes, so familiarization sessions with the test would be necessary to improve its relative reliability. The data obtained can serve as a reference for teams belonging to the same league, as well as to analyze substantial minimal changes outside the intratest noise, according to the reported CVs. © JPES.